The role of adaptive leadership in achieving strategic alignment in healthcare organizations: A field study on hospitals in the Riyadh region - Alharbi, Mohammed Atiah (Edelweiss Applied Science and Technology, 2026)
This study examines the role of adaptive leadership in achieving strategic alignment within healthcare organizations in Riyadh, Saudi Arabia, addressing the critical need for leadership frameworks capable of navigating rapid healthcare transformations. A quantitative research design was employed using a structured questionnaire distributed to healthcare professionals across public and private hospitals in Riyadh. Data from 312 valid responses (out of 327) were analyzed using descriptive statistics, correlation analysis, and multiple regression to assess relationships between adaptive leadership dimensions and strategic alignment. Results revealed high levels of both adaptive leadership practice and strategic alignment, with a statistically significant, strong positive correlation (r > 0.70, p < 0.001) between the constructs. Key adaptive leadership dimensions, observation, interpretation, learning ability, innovation, and environmental leadership, emerged as significant predictors of strategic alignment, collectively explaining substantial variance in alignment outcomes. Adaptive leadership serves as a critical enabler of strategic alignment in dynamic healthcare environments, with leaders' ability to observe, interpret, learn, innovate, and navigate environmental complexities directly influencing organizational strategic coherence. Healthcare administrators should prioritize developing adaptive leadership competencies through targeted training programs, establish mechanisms for continuous environmental scanning, and integrate adaptive practices into strategic planning processes to enhance organizational responsiveness and sustained performance in evolving healthcare landscapes.